2007 GUIDELINES FOR THE MANAGEMENT OF ARTERIAL HYPERTENSION (BEGINNING) (Рациональная фармакотерапия в кардиологии)
The Task Force for the Management of Arterial Hypertension of the European Society of Hypertension (ESH) and of the European Society of Cardiology (ESC).